PENGARUH PEMBERIAN REBUSAN DAUN SALAM (Syzygium polyanthum) TERHADAP KADAR ASAM URAT PADA LANSIA - Mira Andika, Febriyanti (Menara Ilmu, 2018)
The purpose of this research is to see the effect of bay leaf decoction on uric acid level in elderlyin Kuranji Padang Village in 2016/2017 with Pre-experiment method with one group pretestposttestdesign approach in the test with T-test. The result of this research found the influence ofdecoction of bay leaves to uric acid level in elderly with p value 0.000 (p <0,05). On thisoccasion, the researchers expressed their gratitude to the Head of Kuranji Urban Village andPuskesmas Belimbing Padang, Stikes Mercubaktijaya Padang that has facilitated in research andespecially Directorate of Research and Service to Higher Education Society (DIKTI) which hashelped both in the form of morale and support as well as students who have assisted in thisresearch processKey words: decoction, leaf salam, decrease, uric acid, elderly